2009
DOI: 10.1038/sc.2008.169
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy X-ray absorptiometry overestimates bone mineral density of the lumbar spine in persons with spinal cord injury

Abstract: Background: Bone mineral density (BMD) of the lumbar spine (L-spine) has been reported to be normal or increased in persons with chronic spinal cord injury (SCI). Objective: To determine BMD of the L-spine by dual-energy X-ray absorptiometry (DXA) and quantitative computerized tomography (qCT) in men with chronic SCI compared with able-bodied controls. Design: Cross-sectional, comparative study. Setting: Clinical research unit, Veterans Affairs Medical Center, Bronx, NY, USA and Kessler Institute of Rehabilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 23 publications
4
24
0
Order By: Relevance
“…These reports question the method used for testing BMD, showing that the standard method of testing may be misleading. The studies have revealed that the standard posteroanterior dual-energy X-ray absorptiometry overestimates BMD, whereas lateral dual-energy X-ray absorptiometry and quantitative computed tomography scans are more reliable indicators of osteoporosis in SCI patients [28][29][30]. These more recent findings seem to confirm declining bone densities in the axial skeleton that is certainly consistent with the clinical course in some of the patients from our experience.…”
Section: Bone Mineral Densitysupporting
confidence: 82%
See 1 more Smart Citation
“…These reports question the method used for testing BMD, showing that the standard method of testing may be misleading. The studies have revealed that the standard posteroanterior dual-energy X-ray absorptiometry overestimates BMD, whereas lateral dual-energy X-ray absorptiometry and quantitative computed tomography scans are more reliable indicators of osteoporosis in SCI patients [28][29][30]. These more recent findings seem to confirm declining bone densities in the axial skeleton that is certainly consistent with the clinical course in some of the patients from our experience.…”
Section: Bone Mineral Densitysupporting
confidence: 82%
“…The theory is that the sustained weight bearing on the spine in the sitting position helps to maintain the bone density [21,22,27]. However, recent reports have challenged the notion that the axial skeleton is spared loss of BMD in SCI patients [28][29][30]. These reports question the method used for testing BMD, showing that the standard method of testing may be misleading.…”
Section: Bone Mineral Densitymentioning
confidence: 94%
“…CT has the advantage of measuring trabecular bone and avoids the overestimation of BMD by DXA due to degenerative spine disease and increased tissue density (39,40). QCT may be a better predictor of fracture risk than DXA, which is more commonly used in clinical practice (41,42).…”
Section: Original Researchmentioning
confidence: 99%
“…LS preservation is evident in the comparable LS BMD of non-SCI controls. Alternatively, DXA has been found to overestimate the LS BMD in SCI due to confounding osteophytes or heterotrophic ossification (Bauman et al, 2009), and may mask bone loss following injury.…”
Section: Discussionmentioning
confidence: 99%